Pengemasan Iklan Makro Influencer Scarlett Whitening di TikTok untuk Membangun Brand Awareness - Ima Maisyatul Mardiyah; Sheila Lestari Giza Pudrianisa (Jurnal Mahasiswa Komunikasi Cantrik, 2022)
Nowadays, product marketing is now turning to digital media with the development of technology. TikTok is an application that is currently being used by Indonesian Indonesian brands to market their products (Kantar, 2020). One local brand that uses TikTok as its product marketing is Scarlett Whitening. Working with influencers to package ads with six elements, according to (Rossiter and Percy in Bloom and Boone, 2006) to increase brand awareness on TikTok. Based on this background, researchers are interested in conducting research with a focus on how to package Scarlett Whitening macro influencer advertisements on TikTok to build brand awareness. Research with the qualitative descriptive method using constructivist paradigm. The results of this study are the elements of heard words (scented and brightening), Seen words (Glutathione and Niacinamide), picture (products that are always displayed), Movement (movements using products that are always displayed). However, it was found in this study that the elements of music and color are only supporting elements in introducing products from Scarlett Whitening which remain in the endorsement, but because they do not have a characteristic color or musical jingle so they are not effective in introducing the product. Of the four elements of effective advertising packaging, this advertising packaging is at the brand awareness level in the brand recall stage. Because advertising packaging made by macro influencers is Scarlett Whitening's strategy in reminding consumers of their products.